ANALISIS PENGARUH JUMLAH PRODUKSI DAN NILAI TUKAR TERHADAP VOLUME EKSPOR KOMODITAS UTAMA SEKTOR PERIKANAN TANGKAP LAUT TAHUN 2014-2023 - Fadhil Muhammad; R.A. Norromadani Yuniati; Arie Indartono (Proceeding Maritime Business Management Conference, 2024)
Indonesia, as the largest archipelagic country, has abundant maritime economic potential. The capture fisheries sector plays a vital role in the national economy, especially in export and import activities. This study aims to analyze the influence of production volume and exchange rates on the export volume of major marine capture fisheries commodities. This research employs a quantitative causal approach using secondary data from the period of 2014-2023 (on a quarterly basis). The statistical technique used is multiple regression analysis. The results of the study indicate that production volume and exchange rates have a significant simultaneous effect on the export volume of major marine capture fisheries commodities. Partially, the exchange rate significantly affects export volume, while production volume does not have a significant effect on export volume. This indicates that an increase in production volume is not the main driver of rising export volume. On the other hand, an increase in exchange rates makes prices more competitive in international trade, leading to an increase in export volume..